Temporal and spatial variability of environments drive the patterns of species richness along latitudinal, elevational, and depth gradients - Kolomiytsev, Nikolay; Poddubnaya, Nadezhda (Biological Communications, 2018)
This paper seeks to shed light on the primary causes of the latitudinal cline in species diversity, the asymmetry in species richness between the northern and southern hemispheres, and various patterns of species richness along mountain and continental slopes, which are at present of central interest in ecology. To that end, we restate, further develop and unify Janzen’s ideas about the higher fidelity of tropical organisms to their habitats; the notions of Sanders on temporal and spatial variations of environment and their impact on the breadth of species adaptations; the hypothesis of latitude-niche breadth and niche overlap; the theories of climatic stability, competitive exclusion and competitive divergence with the incorporation of some elements of the gradient model of diversification. We argue that during adaptation to a wide range of the same environmental factors in time, the high latitude species also become adapted to a wide range of those factors in space. As a result, they form not only very wide, but also widely overlapping ecological niches. This eventually leads to the competitive extinction of many species and a general impoverishment of biota. In contrast, relatively stable environments allow species to move more and more towards specialization with a simultaneous narrowing of their ecological niches that in turn leads to a reduction of niche overlap and greater species packing in communities. In tropical mountains and on the continental slope, where the environment is stable enough, the degree of its differentiation depends mainly on the steepness of slope. And since the steepest slopes tend to be located at intermediate elevations and intermediate bathyal depths, it is there that there are conditions for the highest specialization. These ideas can provide a framework for new approaches to biodiversity conservation of different regions.